Comparing the performance of four commercial microdiets in an early weaning protocol for European seabass larvae (Dicentrarchus labrax). (10th October 2021) - Giebichenstein, Jan; Giebichenstein, Julia; Hasler, Mario; Schulz, Carsten; Ueberschär, Bernd
Abstract: The promise of an off‐the‐shelf, microparticulate diet for first feeding marine larval fish is still one of the 'holy grails' of the hatchery manager. Replacing the laborious live feed production facilities with high‐quality microdiets will greatly increase marine larval production, improve hatchery consistency and will help in cost reduction in fry production. Over the last decades, many scientific and industrial efforts have focussed on developing microparticulate diets to reduce or replace the use of live feed for growing marine fish larvae in hatcheries. However, in most professional hatcheries, an extended live feed period is still the standard procedure. Thus, this study aimed to compare the performance of four state‐of‐the‐art commercially available microdiets used in an early weaning protocol to the standard Artemia‐based feeding. European seabass larvae were used as a model organism. The three most relevant parameters, survival, growth and deformities were used for the performance‐rating of the four different microdiets. The results of the study depict that early weaning of European seabass between 15 and 20 days post‐hatching (dph) onto the commercially available microdiets still result in lower survival, reduced growth and an increase in deformities in the early‐weaned treatments. Nevertheless, one microdiet outperformed the others in this study, resulting in significantly fewer deformed larvae and improved growth. However, larvae fed with Artemia only still yielded the best results considering growth, survival and deformities.